Measuring decent work in self-managed cooperatives: the Costa Rica case - Villalobos Rodríguez, Gerardo (2020)
Costa Rica has extensive experience in the development of cooperatives, which have occupied an important place in the country’s development strategies, generating a significant volume and diversity of initiatives. Historically, cooperatives have had an impact on human development through job creation and reduction of poverty and inequality. On the other hand, the concept of decent work is an integral approach to work and its promotion also means changing the way the global economy works so that its benefits reach more and more people. The objective of this article is to measure the variable of decent work in Costa Rica self-managed cooperatives.